Application of the Gurnham equation in characterizing the compressibility of fonio and sweet potato starches and their paracetamol tablet formulations (2018)
Background: A number of empirical relationships have been proposed to describe the compaction of pharmaceutical materials, among them are the Heckel, Kawakita and Gurnham equations. Objective: To characterize the compressibility of fonio, sweet potato and corn starches and their paracetamol formulations using the Gurnham and Kawakita equations, and to determine the complementarity of these equations. Materials and Methods: Starches were extracted from fonio (Digitaria exilis) grains and sweet potato (Ipomea batatas) tubers and modified by acid hydrolysis for 96 h. Paracetamol formulations containing 2.5–10.0 %w/w starch binders were prepared by wet granulation. Packing and compaction properties of native and modified starches and their formulations were determined using tapping procedures. The data obtained was analyzed using the Gurnham and Kawakita equations. Results: The ranking for Gurnham compressibility, c, for the starches was sweet potatocornfonio, which was inversely related to the ranking for Kawakita maximum volume reduction, a and angle of internal flow, θ. There was no clear-cut pattern in the Gurnham compressibility of paracetamol formulation probably due to its multicomponent nature. There was correlation between c, a and θ for all the starches with the modified starches exhibiting higher compressibility than native starches. There appeared to be no correlation between c and Kawakita compressibility index, b. Conclusion: The Gurnham equation appeared useful in characterising compressibility in single component systems and could be used along with Kawakita functions, to gain a better understanding of the deformation of powdered materials under pressure.